PENGGUNAAN MODEL PEMBELAJARAN GROUP INVESTIGATION DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (FIQIH) PADA MATERI PERAWATAN JENAZAH KELAS XI BAHASA 1 DI SMA AN-NUR BULULAWANG MALANG - Luthfi Yasykur; Azhar Haq; Fita Mustafida (VICRATINA, 2019)
The results of the study show 1. Learning planning using the Group Investigation learning model in learning Islamic religious education in the treatment of corpses in Class XI Language I Students of An-Nur Bululawang High School. a). describe basic competencies in the syllabus into the learning implementation plan (RPP), b). Determine the learning media that will be applied. 2. the implementation of learning using the Group Investigation learning model .3. learning outcomes observations that have been applied in implementing learning by giving student learning outcomes tests and student observation sheets in each cycle. 4. Reflection concludes the results of observations and tests of student learning outcomes, there has been an increase or not. In this study the results of student learning tests from the first cycle have increased, which is before the first cycle the value of the average student 66.07. And the average value of cycle 1 obtained by students is 71.07. Whereas in the second cycle it has reached the predetermined standard, which is the average value of 74.06. With the increase in learning outcomes, it can be said that the Group Investigation learning model can increase student motivation which will have an impact on the learning outcomes of class XI Language I students of An-Nur Bululawang High School, especially in PAI (Fiqh) learning.Keyword: Group Investigation learning model, Student learning motivation